X-ray crystallographic investigations of the structures of enzymes of medical and biotechnological importance : a dissertation submitted in partial satisfaction of the requirements for the degree of Doctor of Philosophy in the Department of Biochemistry at Massey University, New Zealand - Kingston, Richard Lawrence (Massey University, 1996)
This thesis is broadly in three parts. In the first, the problem of identifying conditions under which a protein will crystallize is considered. Then structural studies on two enzymes are reported, glucose-fructose oxidoreductase from the bacterium Zymomonas mobilis, and the human bile salt dependent lipase (carboxyl ester hydrolase). The ability of protein crystals to diffract X-rays provides the experimental data required to determine their three dimensional structures at atomic resolution. However the crystallization of proteins is not always straightforward. A systematic procedure to search for protein crystallization conditions has been developed. This procedure is based on the use of orthogonal arrays (matrices whose columns possess certain balancing properties). The theoretical and practical background to the problem is discussed, and the relationship of the presented procedure to other published search methods is considered. The anaerobic Gram-negative bacterium Zymomonas mobilis occurs naturally in sugar-rich growth media, and has attracted much interest because of its potential for industrial ethanol production. In this organism the periplasmic enzyme glucose-fructose oxidoreductase (GFOR) is involved in a protective mechanism to counter osmotic stress. The enzyme is unusual in that it contains tightly associated NADP which is not released during its catalytic cycle. The crystal structure of Z mobilis GFOR has been determined by the method of multiple isomorphous replacement, and refined by restrained least squares methods using data extending to an effective resolution of 2.7 Å. The structure determination reveals that each subunit of the tetrameric protein is folded into two domains, one of which is the classical dinucleotide binding domain, or Rossmann fold. The C-terminal domain is a nine-stranded predominantly antiparallel β-sheet around which the tetramer is constructed. Preceding the Rossmann fold there is a 30 amino acid proline rich 'arm' which wraps around an adjacent subunit in the tetramer. The N-terminal arm buries the adenine ring of the NADP, and may also be involved in stabilization of the quaternary structure of the enzyme. The tight association of NADP is accounted for by the structure. An unsuspected structural relationship has been discovered between GFOR and the cytoplasmic enzyme glucose-6-phosphate dehydrogenase (G6PD). It is proposed that GFOR and G6PD derive from an common ancestral gene, and GFOR has evolved to allow it to function in the bacterial periplasm where it is required. The human bile salt dependent lipase (BSDL) is secreted by the pancreas into the digestive tract, and by the lactating mammary gland into human milk, and is integral to the effective absorption of dietary lipids. It is markedly non-specific, and as its name implies is only active against water-insoluble substrates in the presence of primary bile salts. This differentiates the enzyme from conventional lipases. Diffraction data has been collected from crystals of native BSDL (isolated from human milk), and from crystals of recombinant BSDL (including a truncated variant which lacks a C-terminal heavily glycosylated tandem repeat region found in the native enzyme). The structure of the truncated variant has been partially determined at 3.5 Å resolution, by the method of molecular replacement. The recent collection of a higher resolution (2.8 Å) data set should allow the completion of the structure. The current status of the crystallographic investigations of the human bile salt dependent lipase are reported.
Keywords: Protein structure; Enzymes; Zymomonas mobilis; Bile salt dependent lipase; Carboxyl ester hydrolase; Protein crystallisation; Oxidoreductases